2000
DOI: 10.1366/0003702001948682
|View full text |Cite
|
Sign up to set email alerts
|

Resolution Enhancement in IR Spectra of Carbohydrates by the Deconvolution Method and Comparison of the Results with Low-Temperature Spectra

Abstract: This paper presents infrared (IR) spectra of β-d-glucose, cellobiose, and cellulose in the 1500–850 cm−1 range as well as the results of their deconvolution. Comparison of the results of deconvolution with the IR spectra of the investigated compounds obtained at room and helium temperatures of the sample as well as with the theoretical data has been made. It is shown that the use of the deconvolution method provides a better—compared to the low-temperature spectra—resolution of individual absorption band compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…5 More recently, IR resolution enhancement for carbohydrates was achieved by deconvolution methods, enabling the separation of a larger number of spectral bands for mono-, di-, and polysaccharides. 6 Most noteworthy from an analytical perspective, however, is the observance of vibrational spectral "fingerprints" for individual monosaccharides. A far-infrared study (500-100-cm -1 range) along these lines showed that each saccharide exhibited a characteristic spectral pattern, and development of an "encoding" method based on a sequence of relative intensities enabled the discrimination of different saccharides.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 More recently, IR resolution enhancement for carbohydrates was achieved by deconvolution methods, enabling the separation of a larger number of spectral bands for mono-, di-, and polysaccharides. 6 Most noteworthy from an analytical perspective, however, is the observance of vibrational spectral "fingerprints" for individual monosaccharides. A far-infrared study (500-100-cm -1 range) along these lines showed that each saccharide exhibited a characteristic spectral pattern, and development of an "encoding" method based on a sequence of relative intensities enabled the discrimination of different saccharides.…”
mentioning
confidence: 99%
“…Furthermore, bands characteristic of glycosidic linkages in oligosaccharides have been identified . More recently, IR resolution enhancement for carbohydrates was achieved by deconvolution methods, enabling the separation of a larger number of spectral bands for mono-, di-, and polysaccharides …”
mentioning
confidence: 99%
“…The research on the spectroscopy and conformations of polysaccharides and model systems was subsequently continued [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The IR Fourier and Raman spectra of the basic types of mono-, di-, and polysaccharides and their derivatives were analyzed in detail (together with Polish colleagues from the Institute of Low Temperatures and Structural Studies, Polish Academy of Sciences, Wroclaw).…”
mentioning
confidence: 99%